ลักษณะของครูที่ดี - มัชชิกานัง, พระสุขุม สุขวฑฺฒโก; ชยปุตฺโต (วะบุตร), พระมหาชาญชัย (วารสาร ศึกษาศาสตร์ มมร, 2017)
ครูเป็นผู้มีบทบาทสำคัญในการพัฒนาประเทศชาติ ครูย่อมเป็นที่คาดหวังของสังคม แต่การที่จะเป็นครูดีนั้นไม่ใช่เรื่องง่าย เพราะต้องอาศัยองค์ประกอบหลายอย่าง  ลักษณะครูที่ดีมีหลายแนวคิด สามารถพิจารณาและศึกษาได้จากหลักคำสอนทางพระพุทธศาสนา  แนวพระราชดำรัสของพระบาทสมเด็จพระเจ้าอยู่หัว แนวคิดของนักการศึกษาไทยและตะวันตก   และจากผลการวิจัยต่าง ๆ    อย่างไรก็ตาม ครูที่ดีนั้นจะต้องประกอบด้วยคุณลักษณะดังนี้ มีความรู้ดี  สอนดี  ความประพฤติดี  รับผิดชอบหน้าที่ดี  มีบุคลิกภาพและมนุษยสัมพันธ์ดี  ที่สำคัญที่สุด ครูที่ดีนั้นต้องเป็นผู้ที่ฝึกฝนและพัฒนาได้ โดยมีศรัทธา ความมุ่งมั่น และความรักในอาชีพครู Teachers have important role in the development of the country. Teachers were expected from society but to be a good teacher is not easy it is requiring several elements. There were many ideas of the good teacher characteristics such as from Buddhism doctrines, His Majesty the King, Thai and western educational scholars and from the research study. However, a good teacher should consist of fundamental characteristics for example, knowledgeable, knowing teaching principles, being a role model, responsibility, good personality, friendly. In addition, the goo teacher has able to develop herself as a professional teacher by loving, believing and persevering in her profession.